Do you understand what you’re reading? : lasting religious education as a response to the contemporary challenges in reaching the world for Christ - Kushner, Mario (Array, 2020)
The fundamental thought of the Lausanne congresses and The Cape Town Commitment (TCTC) statement as the final product of the third congress, could be summarized by these words: “The Church needs to evangelize the world.” From that battle cry come the challenges of knowing the Gospel and mastering the skills necessary for implementing that plan. This article points out that both challenges can be overcome only through a consistent educational ministry within local fellowships of believers.